1998
DOI: 10.1111/j.1151-2916.1998.tb02454.x
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐Particle‐Enhanced Crystallite Growth of Thin Films of Barium Titanate Prepared by the Sol‐Gel Process

Abstract: The effects of gold-particle incorporation on the structure of barium titanate (BaTiO 3 ) thin films was investigated. BaTiO 3 thin films (110 nm thick) with different gold concentrations were prepared via sol-gel processing and analyzed using X-ray diffractometry. The diffraction results showed that the crystal structure of the thin films changed from predominantly the cubic phase to the tetragonal phase, and the crystallite size increased as the gold concentration increased. Possible mechanisms for the golde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
(45 reference statements)
4
8
0
Order By: Relevance
“…Moreover, the particles are strongly agglomerated which may affect the properties of the final product [6,7]. To overcome these difficulties and to synthesize nanocrystalline fine particles at relatively lower temperatures, wet chemical methods are being employed [8][9][10]. Among the chemical methods, sol-gel synthe- * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the particles are strongly agglomerated which may affect the properties of the final product [6,7]. To overcome these difficulties and to synthesize nanocrystalline fine particles at relatively lower temperatures, wet chemical methods are being employed [8][9][10]. Among the chemical methods, sol-gel synthe- * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Among all metal NPs, gold is considered as one of the most effective dispersing elements for enhancing the photocatalytic property since it has a remarkable SPR effect and chemical stability [8]. On the other hand, BaTiO 3 with high dielectric constant and refractive index [21] has attracted much attention because of its excellent optical property [22], and the BaTiO 3 thin films can be incorporated with noble metal NPs such as Au. The relevant studies [21e25] about BaTiO 3 films dispersed by Au NPs have been reported, demonstrating an absorption peak due to the SPR effect of Au NPs.…”
Section: Introductionmentioning
confidence: 99%
“…BaTiO 3 (BTO) has attracted much attention with respect to its high dielectric constant and refractive index [20,21], chemical stability, environmental benignity, and excellent optical property [22]. However, the photocatalytic activity of BTO is also suffered by its wide E g (~3.18 eV) [23], which has response only to UV light.…”
Section: Introductionmentioning
confidence: 99%